Swedish steel and global resource colonialism: Sandviken's quest for Turkish chromium, 1925–1950. Issue 3 (2nd September 2017) - Vikström, Hanna; Högselius, Per; Avango, Dag
ABSTRACT: This article analyses Swedish industry's attempts to secure strategic raw materials in an era of global resource colonialism. More precisely, it tells the story of how Sandvikens Jernverk – a leading Swedish steel producer – set out to secure its need for chromium ore during the Interwar Era. Up to the late 1920s, Sandviken sourced its chromium from British and French colonies. However, the company feared the British Empire's growing dominance in the global chromium ore market. In 1928, then, Sandviken joined forces with several other Swedish steel producers, forming a consortium that, with ample help from Swedish foreign policy actors, managed to establish an independent source of chromium ore in Turkey. This project, however, which took the form of an Istanbul-based mining company, made big losses and was abandoned after only a few years. The project failed because of changes in the world chromium market, the global economic crisis, conflicts with the company's Turkey-based managing director and the Swedish reluctance to scale up mining in such a way that the chromium ore might compete with Rhodesian, New Caledonian and Baluchistani ore.